Effects of central or decentralized charging stations for electric buses on route planning and travel time in public transport. A case study of Aachen, Germany. - Böhnen, Carina; Louen, Conny (My University, 2017)
Ziel der Studie ist es, den Einfluss des Ladens von Elektrobussen auf die Nachfrage nach öffentlichen Verkehrsmitteln zu untersuchen. Es werden zwei Szenarien in einer Aachener Fallstudie durch Modellierung der Ladungseffekte in einem makroskopischen Transportmodell analysiert. Das erste Szenario untersucht eine zentrale Positionierung der Ladeinfrastruktur. Das zweite Szenario analysiert eine dezentrale Positionierung. Die Analyse der Szenarien hat gezeigt, dass die Ladezeit ein wichtiger Faktor ist. Eine längere Reisezeit wirkt sich erheblich auf die Nachfrage aus. Die Verlängerung der Verweildauer am zentralen Busbahnhof wirkt sich negativ auf die Nutzung des öffentlichen Verkehrs aus.

Public buses are well-suited to electrification (Folkesson et. al, 2003). Electric drive systems have advantages over conventional technologies, for example lower travelling costs, a higher level of energy efficiency, and the chance to reduce emissions (Imaseki, 1998; Electric Power Research Institute, 2007a; Electric Power Research Institute, 2007b; Sioshansi and Denholm, 2009; Sioshansi et al., 2010; Doucette and McCulloch, 2011; Sioshansi and Miller, 2011; Liu et al., 2013; Brouwer et al., 2013; Paulley et al., 2004). Additionally, their operation is easy to plan. Public buses usually run in urban areas in which diesel-powered buses cause air and noise pollution, thus affecting the local quality of life. Financial support and public visibility help spread the new technology. In order to render the use of electric buses in public service possible, the battery needs to be charged during operation. Setting up charging infrastructure is prerequisite for the successful use of electric vehicles (Boulanger et al., 2009; Hatton et al., 2009; Silvester et al., 2009). Different concepts need to be considered when selecting sites for the charging stations. Installing the infrastructure centrally may yield higher efficiency of the stations but is likely to cause operational problems using the turning time at a scheduled route s terminal stop is easier to organize but requires more charging infrastructure. The vehicles themselves add further restrictions due to their limited cruising range. But how do the different concepts affect demand or transportation companies operation planning? Is it even possible to use electric buses in the existing public transport networks using central or decentralized charging and the existing vehicle scheduling without further ado? This paper analyzes the positioning of charging infrastructure for electric buses. The objective is to study the influence of charging electric buses on the demand for public transport. Therefore we analyze two scenarios in a case study of Aachen by modelling effects of charging in an macroscopic transport model. The first scenario explores a central positioning of the charging infrastructure. The second scenario analyzes a decentralized positioning. The analysis of the scenarios has shown that charging time is critical. A longer travel time significantly impacts demand. Extending the dwell time at the central bus station negatively affects public transport use: Use declines from 9.2% to 2.3% and is mainly shifted to private transport. In order to keep up the current level of quality, the transport companies would have to adapt their planning. That way, passengers could, for example, change from an empty electric bus to a charged one. Waiting for the buses to charge has proved to have a much stronger negative impact on demand than having to change to another bus. Aside from affecting demand, central charging would require an adaption of the schedules and would thus also impact the timetable and vehicle scheduling of transport companies. In addition, central charging would pose a logistic challenge and would require an improvement of the queuing policies (De Filippo et al., 2014). The analysis of the timetable and vehicle scheduling has shown that decentralized charging is easier to integrate into the existing structures of local public transport. Decentralized charging using the buses turning time comes with the advantage that the charging process does not affect the travel time provided the cycle plan is adapted accordingly and a sufficiently high charging speed is achieved. For example, the minimum turning time in Aachen is 3 minutes on average. In order to operate the charging infrastructure at maximum capacity, the ends of routes could be combined. In Aachen, radial routes are especially suited to the use of electric buses and to combining the terminal stops. When it comes to network planning in Aachen, this type of route, at an average 8.66 km, a duration of 34:34 mm:ss, and a turning time of 09:03 mm:ss, should be preferred to the other types. In addition, radial routes often have a common origin so that some of the routes already share a terminal stop. The concepts need to be adapted and reviewed individually for each city. Whether the infrastructure can be integrated into each urban design needs to be verified as well. We may conclude that successfully integrating the charging process into the existing structures of public transport requires a complex and holistic concept that takes numerous aspects into account.
Keywords: Öffentlicher Verkehr; Busverkehr; Elektroantrieb; Ladegerät; Ladestation; Dezentralität; Zentralität